2020
DOI: 10.1111/jdv.16964
|View full text |Cite
|
Sign up to set email alerts
|

Time to relapse after tildrakizumab withdrawal in patients with moderate‐to‐severe psoriasis who were responders at week 28: post hoc analysis through 64 weeks from reSURFACE 1 trial

Abstract: Background As treatment interruptions occur during psoriasis management in clinical practice, it is important to know the duration of clinical response after treatment withdrawal. Objectives To report time to and predictors of relapse in patients who were tildrakizumab 100 and 200 mg responders (≥75% improvement in Psoriasis Area and Severity Index, PASI 75) at week 28 re‐randomized to placebo from reSURFACE 1 trial. Methods Post hoc analysis of adult patients with moderate‐to‐severe plaque psoriasis from a 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…In the VOY-AGE 2 trial, 182 out of 375 patients were randomized to guselkumab withdrawal with a median time to loss of PASI 90 at 23 weeks after the last dose [42]. The median time to loss of PASI 90 in the reSURFACE 2 trial was 28 and 32 weeks after the last dose of tildrakizumab 100 and 200 mg [80]. Finally, the median time loss of PASI 90 was 42 weeks after the last dose with risankizumab in the IMMhance trial [57].…”
Section: Discussionmentioning
confidence: 99%
“…In the VOY-AGE 2 trial, 182 out of 375 patients were randomized to guselkumab withdrawal with a median time to loss of PASI 90 at 23 weeks after the last dose [42]. The median time to loss of PASI 90 in the reSURFACE 2 trial was 28 and 32 weeks after the last dose of tildrakizumab 100 and 200 mg [80]. Finally, the median time loss of PASI 90 was 42 weeks after the last dose with risankizumab in the IMMhance trial [57].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate analysis of the AMAGINE-2 and -3 trials, a significant association was observed between the PASI response level and achievement of DLQI 0/1, regardless of treatment arm. More patients who achieved PASI 100 (complete resolution of all disease) than PASI 90 to < 100 also achieved DLQI 0/1 (83.5 vs. 64.3%) [ 19 ]. In the previous phase II trial of brodalumab, patients who achieved total skin clearance (PASI 100) reported greater HRQoL improvements than those who were responders but were not clear of disease (PASI 75 to < 100) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The median time to loss of PASI 75 from 28 weeks was 142 and 172 days with 100 and 200 mg dosing, respectively. Increase in body mass index and an increase in disease duration were associated with relapse ( 110 ).…”
Section: Efficacy Of Tildrakizumab In the Treatment Of Psoriasis: Detailed Review Of Clinical Trial Datamentioning
confidence: 99%